Improving EFL Learners’ Speaking Fluency through Peer Discussion Activities - Fakhra Tabqiya Rahman; Keke Sri Mulyani; Hani Hanifah Amaliah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
This study aims to investigate the effectiveness of peer discussion activities in improving the speaking fluency of EFL learners, to explore learners’ perceptions of peer-based speaking practice, and to identify the pedagogical factors that influence its successful implementation. Key concepts underlying this research include speaking fluency as a core component of communicative competence, Communicative Language Teaching, and socio-constructivist learning. A mixed-methods research design was employed, combining quantitative and qualitative approaches. The participants were Grade VIII students in an Indonesian junior high school. Data were collected through speaking fluency tests administered before and after the intervention, learner perception questionnaires, and classroom observations during peer discussion activities. The findings indicate that structured peer discussion activities significantly improved learners’ speaking fluency, as evidenced by increased speech rate, reduced hesitation, and smoother speech continuity. Learners also reported positive attitudes toward peer discussion, particularly in terms of reduced speaking anxiety, increased confidence, and greater classroom engagement. However, the study faced challenges related to limited intervention duration and a relatively small sample size. Based on these findings, the study recommends the systematic integration of peer discussion activities into EFL speaking instruction, with careful attention to task design and discussion format. Contribution:This study contributes to EFL pedagogy by providing empirical evidence on the role of peer discussion in developing speaking fluency and by reinforcing communicative and socio-constructivist frameworks within the context of junior high school EFL instruction.